PENGARUH PENGETAHUAN DAN PEMBELAJARAN PERATURAN PERPAJAKAN TERHADAP KEPATUHAM WAJIB PAJAK DENGAN PERSEPSI SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA UMKM DI KOTA PEKALONGAN) - Murtini, Murtini; Hanafi, Alfi (BAPPEDA Kota Pekalongan, 2015)
THE PURPOSE OF THIS STUDY TO ANALYZE THE INFLUENCE OF KNOWLEDGE AND LEARNING TAX REGULATION ON TAXPAYER COMPLIANCE WITH PERCEPTION AS AN INTERVENING VARIABLE. THE VARIABLES USED INCLUDE TAXPAYER COMPLIANCE AS THE DEPENDENT VARIABLE, KNOWLEDGE AND LEARNING AS AN INDEPENDENT VARIABLE, AND THE PERCEPTION AS AN INTERVENING VARIABLE. DATA OBTAINED THROUGH QUESTIONNAIRES DISTRIBUTED TO THE RESPONDENTS. THE POPULATION OF THIS STUDY IS SMES IN PEKALONGAN WITH A NUMBER OF SELECTED SAMPLE OF 30 SMES. ANALYSIS OF THE DATA USED IS MULTIPLE REGRESSION ANALYSIS WITH SPSS 16 PROGRAM. THE RESULTS OF THIS STUDY INDICATE THAT PARTIAL (1) KNOWLEDGE OF TAXATION HAS NO EFFECT ON TAXPAYER COMPLIANCE, (2) LEARNING TAXATION SIGNIFICANT EFFECT ON TAX COMPLIANCE, (3) KNOWLEDGE OF TAXATION HAS NO EFFECT ON THE PERCEPTION OF THE TAXPAYER, (4) LEARNING OF TAXATION HAS NO EFFECT ON THE PERCEPTION OF TAXATION TAXPAYER, (5) THE TAXPAYER PERCEPTIONS SIGNIFICANT EFFECT ON TAXPAYER COMPLIANCE IN ACCORDANCE PP NO. 46 IN 2013. SIMULTANEOUSLY, KNOWLEDGE AND LEARNING TAXATION HAVE SIGNIFICANT EFFECT ON TAXPAYER COMPLIANCE IN ACCORDANCE PP NO. 46 IN 2013.